Proposed Use of Land and Building Tax as a Fiscal Policy Instrument to Support Flood Disaster Management Financing in DKI Jakarta. Issue 1 (December 2021) - Yahya, I B; Inayati; Sardjono, L F
Abstract: This article discusses a proposal applying an earmarking tax scheme to PBB-P2 in DKI Jakarta Province to support financing and flood disaster management, based on the flood disaster that always occurs every year and has many losses. In addition, the current pattern of financing comes from the APBD or local general fund. This scheme will trigger the potential for discontinuity of budget allocations for flood disaster management. This study aims to identify and compare the practice of financing and handling disasters in other countries. Then it aims to see the advantages and disadvantages of the proposed proposal and explore the policy recommendations that can be given if this proposal is later implemented. By using a qualitative approach, this research is done through in-depth interviews and literature study. The study results found that, there are two financing schemes for flood disaster management, namely (1) national budget and (2) other government funds. Another finding shows that the proposed application of the earmarking tax can legally be carried out in DKI Jakarta. Although, there are advantages and disadvantages, and there are several options for the DKI Jakarta Provincial Government that can be considered if this proposal is later implemented.